Obstacles to the Automation of Building Performance Simulation: Adaptive Building Integrated Photovoltaic (BIPV) design - Nuttasit Somboonwit; Amon Boontore; Yanin Rugwongwan (My University, 2017)
Building Integrated Photovoltaic (BIPV) is one of the most promising renewable energy technologies. A BIPV system as a second layer of building envelopes is useful not only for the electric power generation but also for blocking solar radiation to reduce cooling load. This study aimed to explore the limitations of the automated BPS of an adaptive BIPV case study that its development conducted through a collaboration of a BIM software, a BIM-integrated visual programming environment, and a cloud-based energy analysis. The possible obstacles to BIPV design processes and the potential solutions have been discussed.Keywords: Automated Building Performance Simulation; Adaptive Building; Building Integrated Photovoltaic; Building Information Modelling; Parametric ModellingISSN: 2398-4287© 2017. The Authors. Published for AMER ABRA by e-International Publishing House, Ltd., UK. This is an open access article under the CC BYNC-ND license (http://creativecommons.org/licenses/by-nc-nd/4.0/). Peer–review under responsibility of AMER (Association of Malaysian Environment-Behaviour Researchers), ABRA (Association of Behavioural Researchers on Asians) and cE-Bs (Centre for Environment-Behaviour Studies), Faculty of Architecture, Planning & Surveying, Universiti Teknologi MARA, Malaysia.
Keywords: Building Integrated Photovoltaics; Building Information Modeling; Building Automation; Building model; BIM and Construction Integration